Análise das interpretações do governo Evo Morales: o legado histórico e o poder nacional-indígena - Aguiar, Jórissa Danilla Nascimento (2012)
This work aims to analyze the interpretations about Evo Morales' government in Bolivia. For such, it proposes a theoretical reclaim of Marxism in Latin America, as well as of Bolivian political history since the 1952 Revolution, going through the crisis in Pacted Democracy intensified in the five-year conjuncture of struggles started in 2000 up to the election and reelection of Morales. It departs from an empirical prior conjecture taken from a qualitative analysis and a broad literature review to analyze the different interpretations of the Bolivian political process from Marxist theoretical matrices. After this historical recovery and this reading of contemporary Bolivia, it concludes with a consideration about the formation of a possible new block of power in the country, with the retaking of nationalism and Indianism as revolutionary reasons